Spiritualitas Komunal Dayak Sebagai Jalan Pertobatan Ekologis: Refleksi Ekoteologis Dalam Terang Laudato Si’ (International Forum of Researchers and Lecturers, 2025)
The ecological crisis affecting Central Kalimantan reveals systemic environmental degradation, ranging from deforestation and river pollution to peatland destruction caused by massive extractive activities. The impact of this crisis extends beyond ecological damage, disrupting the social, cultural, and spiritual order of the Dayak Indigenous communities. This article aims to reflect on Dayak communal spirituality as a path toward ecological conversion in the light of the encyclical Laudato Si’. Employing a qualitative approach through theological–contextual hermeneutics and library research, this study examines the dialogue between Dayak cosmology, communal life values, and the Catholic Church’s vision of integral ecology. The findings indicate that Dayak communal spirituality affirms a reciprocal relationship among humans, nature, the community, and the Creator, which resonates with the call for ecological conversion articulated in Laudato Si’. This article argues that integrating Dayak communal spirituality into the Church’s pastoral praxis holds transformative potential in fostering ecological awareness, strengthening the inculturation of faith, and encouraging the active participation of the faithful in caring for our common home in a sustainable manner.